Strategi Pembiasaan dan Dampaknya Pada Pembentukan Karakter Religius Siswa di Sekolah Menengah Kejuruan - Abidin, Achmad; Amien, Saiful; Nurhakim, Moh. (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aimed to examine the habituation strategies of religious activities and their impact on students’ religious character development at SMK Muhammadiyah 1 Kemlagi. The research employed a qualitative approach with a case study method to gain an in-depth understanding of the implementation process and the influence of religious habituation within the context of vocational education. Data were collected through interviews, observations, and documentation involving teachers, educational staff, and students from various grade levels. The findings indicated that routinely and structurally conducted religious habituation—such as congregational prayers, Qur’anic recitations (tadarus), religious sermons (pengajian), and the management of infaq funds—significantly contributed to instilling spiritual and social values that shaped students’ character. These activities enhanced discipline and responsibility and fostered social awareness and sincerity. The success of this habituation was greatly influenced by the role of teachers as moral exemplars and the active involvement of all school elements, including support from students’ parents. However, the study also identified challenges, such as a lack of family supervision, negative social-environmental influences, and excessive use of technology, potentially hindering religious character development. The study recommended strengthening the synergy among schools, teachers, and families to maintain consistency in habituation practices and to manage technology use so that religious values could continue to grow in students’ daily lives.